Prevalence survey and prognosis analysis of hospitalized patients with acute kidney injury:a single-center study - PAN Xin; NIE Qing-qing; GU Jie; ZHAO Deng-wang; DUAN Yan-ya; ZHAO Dan; ZHANG Chun-jiang; YANG Xiao-ping (Linchuang shenzangbing zazhi)
Objective To investigate the prevalence and the prognosis of acute kidney injury(AKI) in our region and to find out the risk factors associated with the outcome.Methods Between Jan.to Dec.2015,all the hospitalized patients in First Affiliated Hospital of Medical College were screened by Laboratory data retrieval system.Our study cohort was comprised of all the patients with AKI defined by latest clinical guidelines of KDIGO for definition of the renal creatinine.The prevalence was retrospectively analyzed.Logistic regression analysis was used to investigate the risk factors of mortality and renal prognosis.Results Of all the 58 444 hospitalized patients,609 patients suffered from AKI with the prevalence being 1.04%.The ratio of male to female was(2.07:1),and age was(66.3±16.1) years old.by KDIGO criteria,40.9%(n=249) had stage 1,43.2%(n=263) had stage 2 and 15.9%(n=97) had stage 3.The prerenal,intrarenal and postrenal reasons for hospitalized patients with AKI accounted for 70.6%(n=431),21.5%(n=131),and 7.9%(n=48),respectively.On the day 7 after AKI,the mortality rate was 25.5%(155/609).In the final observation,the mortality rate was 29.1%(177/609),complete renal unrecovery rate was 29.9%,partial renal recovery rate was 41.2%,complete renal recovery rate was 18.7%,and the renal function couldn’t be judged in 10.2%patients due to undetermination of creatinine values.Multivariate logistic regression analysis showed that the independent risk factors for mortality were age(OR = 1.598),AKI stage(OR= 1.538),coma(OR= 2.659),and chronic liver disease(OR= 2.134).Organ failure except kidney(P<0.01,OR= 2.548,95%CI:1.717~3.783) was the independent risk factor for renal unrecovery.Conclusions AKI is an increasingly common and potentially catastrophic complication in hospitalized patients.Age,AKI stage,coma,and chronic liver disease were the independent risk factors for mortality.Organ failure except kidney was the independent risk factor for renal unrecovery.AKI should not be viewed as a self-limited disease process from which most patients eventually recover but rather as a significant risk factor for long-term morbidity and mortality following hospital discharge.